การจัดการทรัพยากรเพื่อลดเวลาในงานเทคอนกรีตด้วยวิธีการสร้างแบบจำลองและการจำลองสถานการณ์ในระบบคอสมอส - ดำริห์อนันต์ จิรวัฒน์; ปานรังศรี ธนิถา (Thai Journal of Science and Technology, 2018)
Abstract This research involves the process analysis and the resource management of a concrete-placing operation by means of simulation using COSMOS simulator through COSMOS models. The construction process of a certain part of a Gas Separation Unit in Rayong Province was studied. This research presents resource management, modeling concepts, a simulation model and simulation results of the construction operation under study. The simulation outcomes indicated that 3 trucks should be employed in the operation and the amount of concrete to be placed per day should be 50 m3 for the process to be optimal. The results were then implemented on the real operation of the project and found to be appropriate. The efficiency of the overall construction operation was improved which can be seen from the increment of the actual work performed when comparing with the plan. The model presented in this research was able to be used for the simulation of the operation under study. The simulation outcomes was successfully implemented which resulted in efficient manipulation of the resources employed in the real process. Keywords: modeling; simulation; COSMOS; construction operation; concrete placing; Petri nets